Effect of primary lesions in cytoskeleton proteins on red cell membrane stability in patients with hereditary spherocytosis - Vercellati, Cristina; Marcello, Anna Paola; Fattizzo, Bruno; Zaninoni, Anna; Seresini, Agostino; Barcellini, Wilma; Bianchi, Paola; Fermo, Elisa (Frontiers in Physiology, 2022)
We investigated by targeted next generation sequencing the genetic bases of hereditary spherocytosis in 25 patients and compared the molecular results with the biochemical lesion of RBC membrane obtained by SDS-PAGE analysis. The HS diagnosis was based on available guidelines for diagnosis of congenital hemolytic anemia, and patients were selected because of atypical clinical presentation or intra-family variability, or because presented discrepancies between laboratory investigation and biochemical findings. In all patients but 5 we identified pathogenic variants in SPTA1, SPTB, ANK1, SLC4A1, EPB42 genes able to justify the clinical phenotype. Interestingly, a correspondence between the biochemical lesion and the molecular defect was identified in only 11/25 cases, mostly with band 3 deficiency due to SLC4A1 mutations. Most of the mutations in SPTB and ANK1gene didn’t hesitate in abnormalities of RBC membrane protein; conversely, in two cases the molecular lesion didn’t correspond to the biochemical defect, suggesting that a mutation in a specific cytoskeleton protein may result in a more complex RBC membrane damage or suffering. Finally, in two cases the HS diagnosis was maintained despite absence of both protein defect and molecular lesion, basing on clinical and family history, and on presence of clear laboratory markers of HS. The study revealed complex relationships between the primary molecular lesion and the final effect in the RBC membrane cytoskeleton, and further underlines the concept that there is not a unique approach to the diagnosis of HS.